1980
DOI: 10.1002/pssb.2221000130
|View full text |Cite
|
Sign up to set email alerts
|

Creation and Destruction of X Centres in Alkali Halides by X‐Radiation

Abstract: The production (qand destruction efficiencies cf X, centres in NaCI, KCl, KBr, and KI by X-radiation versus the irradiation temperature (in the range of 80 to 320 K) are investigated by optical absorption and thermoluminescence methods. Both, the increase (80 to 150 K) and decrease (200 to 250 K) of qs3 in KBr and KI a t the adsorbed dose of lOlS to loz1 eV cm-3 are shown to be in correlation with the F-centre creation efficiency ( 7~) .I n chlorides q p does not decrease with qx7 and these crystals are charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The accumulation of various color centers was most comprehensively studied in the alkali halides and some simple oxides. In particular, clear effects of temperature, crystal structure, impurities and the type of radiation [34,35,36,37,38,39,40,41] were reported. Moreover, it has been more than once demonstrated that the saturation effects are most easily observed in case of ion irradiation.…”
Section: Theory and Main Resultsmentioning
confidence: 99%
“…The accumulation of various color centers was most comprehensively studied in the alkali halides and some simple oxides. In particular, clear effects of temperature, crystal structure, impurities and the type of radiation [34,35,36,37,38,39,40,41] were reported. Moreover, it has been more than once demonstrated that the saturation effects are most easily observed in case of ion irradiation.…”
Section: Theory and Main Resultsmentioning
confidence: 99%
“…Jn conclusion, on the ground of previous [a, 8, 10, 17, 181 and present studies, we consider the growth scheme of halogen associates in KBr typical of the X-irradiation a t temperatures above 200K (Fig. 9).…”
Section: Discussionmentioning
confidence: 96%
“…9). At these temperatures the elementary Br; centres (V, and V, centres) in pure KBr are unstable under irradiation [17] and only larger associates such as Br;, Bry, A,, A,, etc. survive.…”
Section: Discussionmentioning
confidence: 98%